Carbon Microstructures Synthesis in Low Temperature Plasma Generated by Microdischarges - Arkadiusz T. Sobczyk; Anatol Jaworek (Applied Sciences, 2021)
The aim of this paper is to investigate the process of growth of different carbon deposits in low-current electrical microdischarges in argon with an admixture of cyclohexane as the carbon feedstock. The method of synthesis of carbon structures is based on the decomposition of hydrocarbons in low-temperature plasma generated by an electrical discharge in gas at atmospheric pressure. The following various types of microdischarges generated at this pressure were tested for both polarities of supply voltage with regard to their applications to different carbon deposit synthesis: Townsend discharge, pre-breakdown streamers, breakdown streamers and glow discharge. In these investigations the discharge was generated between a stainless-steel needle and a plate made of a nickel alloy, by electrode distances varying between 1 and 15 mm. The effect of distance between the electrodes, discharge current and hydrocarbon concentration on the obtained carbon structures was investigated. Carbon nanowalls and carbon microfibers were obtained in these discharges.